Production of Transparent Solid Antibacterial Soap from Palm Oil Using Eco-Enzyme - Murdikaningrum, Galu; Ramadhan, Adisti; Astari, IIs Ananda; Ningtyas, Rani Pramudyo; Hutagalung, Johannes Martua (Universitas Insan Cendekia Mandiri, 2024)
Abstract: Hygiene is essential in daily life, and soap is vital for effectively cleansing contaminants and bacteria from the skin. Recent innovations in soap-making, including the development of transparent soaps, aim to enhance both functionality and aesthetic appeal. This study explores the incorporation of eco-enzyme, derived from the fermentation of kitchen waste such as fruits, vegetables, sugar, and water, into transparent antibacterial soap. Eco-enzyme contains lipase, trypsin, and amylase, which are effective in inhibiting pathogenic bacteria. The adoption of eco-enzyme not only enhances the sustainability of soap production but also promotes the efficient use of organic waste. This research conducted a laboratory-based experimental investigation to evaluate the effectiveness of eco-enzyme in the production of transparent solid antibacterial soap using palm oil. The process involved several stages: preparation of raw materials, soap production, and subsequent analysis. The results demonstrated that the soap met SNI standards with water content ranging from 12% to 17%, a pH between 9.57 and 9.81, and free fatty acids ranging from 0.9% to 1.7%. The inhibition zone for Staphylococcus aureus was 7.81 mm, indicating a moderate antibacterial effect. These findings suggest that eco-enzyme provides a bacteriostatic effect, inhibiting bacterial growth without necessarily killing the bacteria, and highlight its potential for developing sustainable and effective antibacterial products. Keywords: antibacterial soap, eco-enzyme, Staphylococcus aureus.